S8 Effect of the VitaBreath device on exercise capacity & symptoms in COPD. (December 2018) - Chynkiamis, N; Armstrong, M; Lane, N; Hartley, T; Bourke, S; Vogiatzis, I
Abstract : Introduction: Non-Invasive Ventilation (NIV) prolongs exercise tolerance in COPD patients, but its use is limited by practical issues. The VitaBreath device (Philips, Respironics) provides Bi-level Positive Airway Pressure (PAP) support, aiming to unload the respiratory muscles and reduce breathlessness. However it can only be used during the resting periods. Aim: To assess the effect of the VitaBreath device compared to the pursed lip breathing technique (PLB) on exercise tolerance and symptoms of breathlessness and leg discomfort during two different protocols of intermittent exercise in COPD. Methods: Twenty Four patients (mean ±SD, age: 67±8 years; FEV1 : 46%±18% predicted) initially performed an incremental cycling test to the limit of tolerance (Wpeak). They were then randomly allocated to a high intensity intermittent protocol (HI: 2 min work at 80% Wpeak alternated with 2 min rest; n=13), or a moderate intensity intermittent protocol (MOD: 6 min work at 60% Wpeak alternated with 2 min rest; n=11), both sustained to the limit of tolerance. Two exercise tests were then performed, using PLB or the VitaBreath device in balanced order during the first minute of each 2 min rest period. Results: Compared to PLB, use of the VitaBreath device increased exercise tolerance (HI: by 5.2±5.9 min; p=0.008 and MOD: by 5.8±6.6 min; p=0.016). At the limit of exercise tolerance using the VitaBreath device compared to PLB there were reductions in Borg 1–10 breathlessness scores (HI: from 4.8±1.2 to 3.9±1.4; p=0.050 and MOD: from 4.0±1.1 to 3.2±1.1; p=0.004), and Borg 1–10 leg discomfort scores (HI: from 4.5±1.5 to 4.0±1.8; p=0.027 and MOD: from 4.1±1.2 to 3.3±1.6; p=0.011). At the limit of tolerance inspiratory capacity with the use of the VitaBreath device was greater compared to PLB only during HI (2.34±0.78 L vs 2.20±0.78 L; p=0.042), indicating less dynamic hyperinflation. Compared to PLB, use of the VitaBreath device was associated with greater mean cardiac output (HI: by 0.3±1.1 litres/min; p=0.035 and MOD: by 0.8±0.9 litres/min; p=0.045) and greater mean systemic O2 delivery (HI: by 70±40 ml/min; p=0.040 and MOD: by 160±40 ml/min; p=0.040). Conclusions: Use of the VitaBreath device increases exercise tolerance by reducing perceived symptoms and improving central and peripheral haemodynamic responses.